2021
DOI: 10.1016/j.phro.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic computed tomography data allows for accurate absorbed dose calculations in a magnetic resonance imaging only workflow for head and neck radiotherapy

Abstract: Highlights The geometry of the synthetic CT is comparable to the CT in the H&N region. Synthetic CT in the H&N region provides similar absorbed dose calculation as the CT. Absorbed dose calculations in the dental region could benefit from using synthetic CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
(33 reference statements)
1
31
0
Order By: Relevance
“…for brain, 65 pelvis 116 in I, and for H&N, thorax, and pelvis in II. 66 In the last month, Palmer et al 198 also reported using a prereleased version of a DL-based sCT generation approach for H&N in MR-only RT. Another essential aspect that needs to be satisfied is the compliance to the currently adopted regulations, 199 where vendors can offer vital support.…”
Section: Benefits and Challenges For Clinical Implementationsmentioning
confidence: 99%
“…for brain, 65 pelvis 116 in I, and for H&N, thorax, and pelvis in II. 66 In the last month, Palmer et al 198 also reported using a prereleased version of a DL-based sCT generation approach for H&N in MR-only RT. Another essential aspect that needs to be satisfied is the compliance to the currently adopted regulations, 199 where vendors can offer vital support.…”
Section: Benefits and Challenges For Clinical Implementationsmentioning
confidence: 99%
“…CT is also essential to achieve accurate radiation dose calculation for radiotherapy [12,18,19]. Several approaches have recently been proposed to generate synthetic CT (sCT) from MR images [20][21][22][23]. However, MR-derived sCT is challenged by the variety of tissue types and bowel gas present in the pelvic region.…”
Section: Introductionmentioning
confidence: 99%
“…The sCT images were generated using the CE approved sCT generation software MRI Planner (v 2.2, Spectronic Medical, AB, Helsingborg, Sweden), previously validated for both brain and head and neck cancer ( 8 , 20 ). The software is deep learning-based and utilizes a 3D deep convolutional neural network to generate sCT images based on Dixon images (fat, water, in-phase and out-of-phase).…”
Section: Methodsmentioning
confidence: 99%